LANGUAGE AND GENDER: A CONVERSATION ANALYSIS IN THE DIFFERENCE OF LANGUAE RELATED TO GENDER - Dian Eka Putri; Kartika Harda Putri; Elviza Yeni Putri (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
There is a proverb says ‘men are from Mars and women are from Venus’. There is also term ‘female language’ and ‘male language’. Those state clearly that men and women are different. Are they really are? To find out, there were several aspects analyzed in this research related to the differences done by women and men in their language (conversation). The aspects were: a) The amount of talk. b) Turn Taking. The data of this study was in form of recorded conversation and its transcription. Both the recorded conversation and its transcription were got from talk bank site  (http://talkbank.org/CABank/ca-data.html). There were three participants in this conversation. They were Joanne, Ken and Lenore. Joanne and Ken were a couple. Lenore was a friend of theirs. in analyzing the data, the researcher acted as key instrument. The first finding was about the amount of talk. It was found that Ken talk the most during the conversation, followed by Joanne and the Lenore. This finding broke the stereotype that men talk less than women. The second finding was about turn-taking. There were two kinds of turn-taking system discussed in this research (other-selection and self-selection). It turned out that Joanne had the smallest amount of other selection but had the highest amount of self-selection. On the other hand, Lenore had the highest amount of other-selection but had the lowest amount of self-selection. It seemed that the amount of other-selection was upsidown to self-selection.